Korespondensi di Kejaksaan Negeri Padang - Nainggolan, Susi Dawati; Syahyuman, Syahyuman (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2012)
The purpose of this research are (1) describe a variety of correspondence on the Padang District prosecutors, (2) describe the maintenance procedures of correspondence in the Padang District Attorney. The data is collected by interviewing the archivists who work in the correspondence field on the Padang District Attorney's Office, it was analized by using descriptive method. Based on the data analysis, it can be concluded as following matters: first, the typesof correspondence on the Padang District Attorney are regular and confidential letter. Second, the procedures letter in Padang District Attorney is same as the existing theory. Keywords: correspondence procedures